LEADERSHIP AND CRISIS BASED ON CONTINGENCY APPROACH AND LEADER'S FATAL FLAWS A CASE STUDY IN X INSTITUTE INDONESIA - Dewi, Yuli Kartika (Jurnal Aplikasi Manajemen, 2020)
The power of a leader is on the impact on the people that he leads, the organization's condition and the sustainability of the organization.Conditions in the organization is a difficult thing to predict. Every decision taken has a different impact. That is where a leader's ability is tested. How a leader in the midst of his limitations must be able to bring himself, his team and his organization in a better direction. This study was analyzed by taking into account factors that exist in the contingency and fatal flaws approach of a leader. The results of the analysis found that a leader who has strong experience, competence, commitment and ability to build and maintain good relationships with his team will be an effective leader and able to bring the organization out of the crisis.